Quality of life in persons living with advanced glaucoma in South India - Gopinath Madheswaran; Subash Sukumar; Evangeline Golda Victor; Saranya Sachi Balasubramaniam; Chinnasamy Balasubramanian (Discover Social Science and Health)
Abstract Purpose Glaucoma can significantly affect visual functions, independence, mobility, and quality of life (QoL), particularly in the advanced stage. Physical health, emotional state, and socioeconomic status can influence the QoL. This study aimed to understand the QoL of glaucoma patients attending tertiary eye hospital in south India. Methods Glaucoma patients from rural/semi-urban region were interviewed using a semi-structured interview guide in their vernacular language to capture the challenges and limitations in their daily lives due to glaucoma. Audio-recorded interviews were transcribed verbatim, and thematic analysis was performed to understand their QoL. Results Twenty patients [75% (n = 15) males] were interviewed, and six themes were identified. Many (75%) sought medical advice after vision disturbances leading to a glaucoma diagnosis. Half (50%) were identified in routine exams, and few self-referred due to positive family history. Adapting was challenging, affecting daily activities, work, mobility, dark adaptation, and medication discomfort. Many (40%) accepted their condition, while a few (25%) struggled with fear, depression, and frustration upon diagnosis, emotional distress, and social isolation. Financial burdens were significant for many due to losing jobs, and few relied on pensions. Adaptive strategies include engaging in physical activity, spending time with family members, and engaging in social activities. Conclusion Patients presenting late with advanced glaucoma to rural/semi-urban eye hospital in India experience significantly affect their QoL. Healthcare providers can better support glaucoma patients by identifying patients with functional and psychological distress using structured questionnaires, creating awareness of the condition and advising them with constructive coping strategies/referrals for counselling.